Biochemical composition and reproductive cycle of the clam Chamelea gallina in the Northern Adriatic Sea: an after-10-year comparison of patterns and changes - Moschino, Vanessa; Rizzo, Giulia; Marĉeta, Tihana; Cernigai, Federica; Masiero, Luciano; Da Ros, Luisa; Marin, Maria Gabriella (Frontiers in Marine Science, 2023)
The study of the relationships between growth patterns, energy reserves and reproduction, and their interdependency with environmental variables is crucial to increase the knowledge of the physiological processes regulating the recruitment and survival of commercially exploited bivalve species. In the present study, the biochemical profile and gametogenic cycle of the striped Venus clam Chamelea gallina monthly sampled in fishing grounds of the Chioggia district in 2001 and 2010 were investigated to identify possible variations that occurred after 10 years and to analyse inter-relationships among the biological parameters with changing environmental conditions. Our results indicated that higher phytoplankton availability and increased water temperature recorded from 2001 to 2010 resulted in higher reserve accumulation, mostly in the form of proteins, carbohydrates and glycogen. An increase was also observed in the calcification rate of the shells, which consequently became heavier in clams collected in 2010. Moreover, in 2010, as for the reproductive conditions, a prolonged spawning period was observed with respect to 2002. Overall results highlighted clear-cut differences in the physiological performances of clams collected in 2001 and 2010, suggesting the importance to monitor changes over time to unveil potential pros and cons for single populations of commercial interest.